2020
DOI: 10.21203/rs.3.rs-40299/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19: A National Survey on Perceived Level of Knowledge, Attitude and Practice among Frontline Medical Professionals in Nepal

Abstract: Background COVID-19 is currently recognized as an emerging public health problem caused by SARS-CoV-2. Thousands of people around the world have been infected since it appeared the very first time in Wuhan. For any epidemics, FMPs are at high risk of infection, and also become the vector for the disease transmission. Inadequate knowledge has been proven to be the causative factor for disease infection & transmission. This study aimed to determine the knowledge, attitude & practice among FMPs, includin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The current study subjects had sufficient knowledge level toward COVID-19 IPC, where almost two-thirds of them scored above the cutoff point set at the mean which was 5.6 out of 6. Similar findings were revealed by a number of studies conducted to determine the KAP among different medical professionals; physicians, nurses, and other paramedics working in the frontline in hospitals, where their study respondents were considered to have sufficient knowledge toward COVID-19 IPC [35], [36], [37].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The current study subjects had sufficient knowledge level toward COVID-19 IPC, where almost two-thirds of them scored above the cutoff point set at the mean which was 5.6 out of 6. Similar findings were revealed by a number of studies conducted to determine the KAP among different medical professionals; physicians, nurses, and other paramedics working in the frontline in hospitals, where their study respondents were considered to have sufficient knowledge toward COVID-19 IPC [35], [36], [37].…”
Section: Discussionsupporting
confidence: 73%
“…Accordingly, almost half of the physicians had positive attitude toward COVID-19 IPC as their mean attitude score was 24.9 (±2.8). Positive attitudes toward COVID-19 IPC among HCWs varied in similar studies, where two researches conducted at Nepal and Nigeria revealed that almost half of their study subjects and around two-thirds of their study population, respectively, had positive attitude toward COVID-19 IPC [34], [37]. However, in a different study conducted in Uganda, only one-quarter of the study subjects had positive attitude toward COVID-19 IPC [43].…”
Section: Discussionmentioning
confidence: 95%
“…A higher level of knowledge is positively associated with the practice of preventive measures and attitudes are also positively associated with preventive behaviors. Nonetheless, the majority of these studies examined the direct effects of knowledge on practicing preventive behaviors ( Afzal et al, 2021 ; Alrubaiee et al, 2020 ; Lau et al, 2020 ; Tamang et al, 2020 ) or attitudes without investigating the indirect effects of knowledge on practices mediated by attitudes to explain the psychological mechanism underlying how individuals engage in behaviors based on their health knowledge. Little is known about the indirect influence of knowledge on practices via attitudes in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Health workers are at the forefront of dealing with COVID-19 and have an important role in controlling the disease. 1 Furthermore, direct service to patients, frequent exposure to pathogens, limited availability of personal protective equipment (PPE), mental stress, fatigue, long working hours, the nonproportionality of total health workers to the patients' increasing number, social stigma and psychological factors cause the workers to be at high risk of being infected with COVID-19. 2,3 In Indonesia, there are 878 health workers infected with COVID-19 based on data from Amnesty International until June 12 2020.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Previous studies have shown that the knowledge, attitudes and behavior of health workers in dealing with COVID19 pandemic have many differences. 1,[14][15][16] The high incidence of health workers' infection with the virus shows the need to analyze the relationship of knowledge, attitudes, and behavior with preparedness to encounter the pandemic that could control morbidity and mortality rates, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%